Current challenges of forming socio-economic model of the city development - Yavorska, Viktoriia; Shynkarenko, Sergii (Journal of Education, Health and Sport, 2022)
The article analyzed current challenges of forming the socio-economic model of city development in the forms of urbanization, its types, consequences, and structural changes in societies.